Comparative Histological Study on Teat of Domestic Animals - Urmila, T. Sai; Ramayya, P. Jagapathi; Lakshmi, M. Santhi; Kumar, R. V. Suresh; Amaravathi, P. (International Journal of Bio-resource and Stress Management, 2024)
The present study was executed at Department of Veterinary Anatomy, College of Veterinary Science, Sri Venkateswara Veterinary University, Tirupati, Andhra Pradesh, India during the period of July, 2020 to October, 2021 to find the possible differences in histology of teat among domestic animals. The study was conducted on teat of domestic animals i.e., 6 adult buffalo, 6 cattle, 15 sheep, 15 goats, 6 dogs and 6 pigs. The wall of the teat consisted of three layers in buffalo, cattle, sheep, goat and pig i.e., outer skin, middle muscular and inner connective tissue layer. But in dog only two layers were present i.e., outer skin and inner fibromuscular layer. Each teat consisted of single teat sinus in buffalo, cattle, sheep and goat, whereas in pig each teat showed two teat sinuses and eleven sinuses in dog. In buffalo and cattle, isolated clusters of glandular structures were seen between the smooth muscle fibers which were absent in sheep, pig and dog. Further, in sheep and goat, accessory glands were noted in the dermis and in middle layer. Sweat glands were noticed only in sheep and goat. In cattle and pig, hair follicles were not distinct and they were surrounded by numerous sebaceous glands. The number of collagen fibers in dermis of teat were more dense in cattle than other domestic animals. Elastic fibers were numerous in dog and moderate in the dermis of teat in buffalo, cattle, sheep and very few in goat.